Peran Guru dalam Menumbuhkan Apresiasi Sastra Siswa Kelas VI SDN 2 Mata IE - Aceh Besar Tahun Pelajajaran 2024/2025 - Hutabarat, Imelda; Suharti, Sri (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research aims to determine the learning strategies used by teachers at SDN 2 Mata Ie-Aceh Besar in fostering student appreciation for literary works, using qualitative research methods, so that data is collected through observation, interviews comparing student work results from 3 meetings. The research results show that in learning activities teachers use strategies learning, namely: 1) reading local literary folk tales loudly and clearly in front of the class entitled "Mentikoh Betuah", 2) using visual and audio media in learning, 3) using school infrastructure in the form of a library. The teacher's various efforts in learning have succeeded in fostering students' appreciation of literary works and students' understanding of the cultural values ​​contained in local literary works. Buru plays an active and creative role in designing interesting and meaningful learning activities so that learning objectives are achieved.